Meta Analisis Penggunaan Media Pembelajaran Online-Offline dan Pengaruhnya terhadap Hasil Belajar Siswa - Ena Suma Indrawati; Lelfita; Ilham Adi Putra; Yeni Nurpatri (Yayasan Perguruan Kampus, 2023)
This study aims to describe articles which related to the development of learning design. It uses a meta-analysis method by using sample of 30 international articles. This meta-analysis research shows the importance of developing learning design such a developing online-offline learning media. While, the learning media which are used related to the students and learning materials’ problems. Based on the data analysis results, they are showed 80% of problems are related to the lack of students’ interest in learning, low of students’ learning outcomes and techniques used by teachers are not adequate for teaching and learning process. The results show that researchers used online media such as e-learning, e-comic, internet-based economics, and 3D animation. The using offline media like applying jigsaw and whole brain techniques. The advantages of using learning media are increasing learning outcomes, learning motivation and students’ understanding.